Analysis Of Hate Speech Against Anies Baswedan In Instagram Comment Sections: A Pragmatics Analysis - Ardana, Putri; Raflis, Raflis (Jurnal Ilmiah Langue and Parole, 2025)
This reserach examines the phenomenon of hate speech directed at Anies Baswedan by Instagram users, with the aim of identifying and analyzing various types of hate speech as well as illocutionary speech acts that appear in comments on the platform. This research employs a pragmatic approach as its analytical framework to identify different types of hate speech and analyze the illocutionary dimension of such speech. The research method used is qualitative, where data is collected and classified based on the content of Instagram user comments. The data subjects analyzed are sentences containing elements of hate speech on Anies Baswedan's Instagram account. Then, researcher use the document technique. The analysis revealed that there are 15 utterances of hate speech in the form of insults, 1 utterance of provocation, and 4 utterance of spreading false news. Additionally, in terms of illocutionary acts, there are 2 categorized as utterance of representative, 6 utterance expressive, and 1 utterance of directive. The findings of this research provide significant insights into the patterns and characteristics of hate speech on social media, as well as its implications for political communication in the digital sphere.